2023
DOI: 10.1111/jcal.12817
|View full text |Cite
|
Sign up to set email alerts
|

Capturing cognitive load management during authentic virtual reality flight training with behavioural and physiological indicators

Abstract: Lay DescriptionWhat is currently known about the subject matter The advantages of VR training systems are clear in the safety‐critical fields. Cognitive load (CL) theory may help design of VR training. CL management is part of the professional competence in these fields. What this paper adds The pilots performed well in CL management in VR flight training. The work experience of the pilot was not associated with the performance. The physiological data improved the explanatory level of the performance. The impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The LF/HF ratio has been used in previous studies as an objective measure of cognitive load: Usui and Nishida (2017) found the LF/HF ratio to be significantly higher during a mental stress task than before or after and Minkley et al (2021) found that LF/HF ratio is related to the self-reported mental effort of the participants. Lämsä et al (2023) used HRV indices, including LF/HF ratio, to study pilot's cognitive load in a VR flight simulation. Kim and Jo (2019) also used the LF/HF ratio as a measure of cognitive load, and concluded that learners' changing cognitive load could be measured and visualised based on this index.…”
Section: Code Description Examplesmentioning
confidence: 99%
“…The LF/HF ratio has been used in previous studies as an objective measure of cognitive load: Usui and Nishida (2017) found the LF/HF ratio to be significantly higher during a mental stress task than before or after and Minkley et al (2021) found that LF/HF ratio is related to the self-reported mental effort of the participants. Lämsä et al (2023) used HRV indices, including LF/HF ratio, to study pilot's cognitive load in a VR flight simulation. Kim and Jo (2019) also used the LF/HF ratio as a measure of cognitive load, and concluded that learners' changing cognitive load could be measured and visualised based on this index.…”
Section: Code Description Examplesmentioning
confidence: 99%